Examining the association between surface bioburden and frequently touched sites in intensive care. Issue 1 (January 2017) - Adams, C.E.; Smith, J.; Watson, V.; Robertson, C.; Dancer, S.J.
Summary: Background: Critical care patients are at increased risk of infection. Near-patient surfaces act as reservoirs of microbial soil, which may contain pathogens. Aim: To correlate soil levels with hand-touch frequency of near-patient sites in an intensive care unit (ICU). Methods: Five sites around each bed in a 10-bed ICU were screened for total microbial soil (cfu/cm 2 ) and Staphylococcus aureus every month for 10 months. Selected sites were infusion pump and cardiac monitor, left and right bedrails, and bed table. Ten 1 h covert audits of hand-touch frequency of these sites were performed in order to provide an average hand-touch count, which was modelled against soil levels obtained from microbiological screening. Findings: Seven of 10 staphylococci were found in conjunction with gross contamination of a specific site ( P = 0.005) and the same proportion from three most frequently touched sites (bedrails and bed table). There was a linear association between four sites demonstrating gross microbial contamination (>12 cfu/cm 2 ) and mean number of hand-touch counts ( P = 0.08). The bed table was handled most but was not the most contaminated site. We suspected that customary placement of alcohol gel containers on bed tables may have reduced microbiological yield. Removing the gel container from one table confirmed its inhibitory effect on microbial contamination after rescreening (19% vs 50% >12 cfu/cm 2 : P = 0.007). Conclusion: Surface bioburden at near-patient sites in ICU is associated with hand-contact frequencies by staff and visitors. This supports the need for targeted hygienic cleaning in a high-risk healthcare environment.